The impact of self-administered acupressure on sleep quality and fatigue among patients with migraine: A randomized controlled trial. (May 2019) - Vagharseyyedin, Seyyed Abolfazl; Salmabadi, Mohaddeseh; BahramiTaghanaki, Hamidreza; Riyasi, Hamidreza
Abstract: Background and aim: Poor sleep and fatigue are among the most common complaints of patients with migraine. These problems can lead to different negative consequences such as headaches. This study aimed to examine the impacts of self-administered acupressure on sleep quality and fatigue among patients with migraine. Methods: This double-blind randomized controlled trial was conducted in 2016 on 76 patients who suffered from migraine without aura. Patients were conveniently selected from the neurology clinic of Valiasr (PBUH) teaching hospital and randomly allocated to either an acupressure (n = 38) or a sham acupressure group (n = 38) group. Data collection instruments were a demographic questionnaire, Pittsburg Sleep Quality Index, and Fatigue Severity Scale. Patients in the acupressure and the sham acupressure groups were trained to apply acupressure on respectively acupoints and sham points thrice weekly at bedtime for four consecutive weeks. The data were analyzed through the Chi-square, the independent-sample t, the paired-sample t, and the ANCOVA tests at the significance level of less than 0.05. Results: After controlling sleep quality mean scores at baseline, no significant difference was found between the sleep quality of the two groups after intervention (P > 0.05). The mean scores of fatigue significantly decreased in both acupressure and sham acupressure groups (P < 0.05). However, the decrease in the acupressure group was significantly greater than in the sham acupressure group (P < 0.05). Conclusion: As a noninvasive non-pharmacological therapy, acupressure can significantly reduce fatigue among patients with migraine.